Millennium Development Goals (MDG) Gap Task Force Report 2009 - Nations Unies (United Nations, 2013)
Further progress has been made towards fulfilling the promises embodied in the Millennium Development Goal 8 (MDG 8). However, the Global Partnership for Development has suffered important setbacks, most of which have arisen from the current state of the world economy which is experiencing its severest downturn since the Great Depression of the 1930s. In the countdown to 2015, urgent responses are needed to bridge the existing implementation gaps to make good on the promises made to achieve the Millennium Development Goals. The 2009 issue of the report by the United Nations Millennium Development Goals Gap Task Force identifies these gaps in detail and provides recommendations to all major stakeholders on how to address these gaps.